Synthesis and Electrochemical Studies of Titanium Dioxide Based Nanostructured Catalysts for Environmental Applications - Chang, Xin (My University, 2016)
Nanomaterials are playing an increasingly important role toward addressing emerging environmental challenges. Heterogeneous catalysis is the best option available for the elimination of environmentally incompatible compounds that reside within contaminated water sources. Among all investigated nanomaterials, TiO2 has proven itself as optimal for various applications such as photocatalysis, electrochromic devices, dye sensitized solar cells, hydrogen production, and sensing. TiO2 is impressive due to its low cost, non-toxicity, chemical inertness, and high efficiency. In spite of having all these excellent properties, the efficient utilization of TiO2 for various applications is limited by its inability to absorb visible light. Due to large band gap, only UV light may be absorbed by TiO2, thus making it minimally efficient when exposed to sunlight, which contains only about 4% in the UV spectrum. An enormous amount of research has been focused on decreasing the band gap of TiO2 in order to increase its efficiency under sunlight. The present research is focused on the development of new techniques to increase the conductivity of TiO2 nanomaterials as well as to decrease its band gap to make it an efficient photoelectrocatalyst. During my PhD study, TiO2 nanostructured materials were fabricated using a facile anodization method. TiO2 nanotubes were synthesized by employing DMSO + 2% HF as an electrolyte. An electrochemical (EC) reduction method was employed to reduce the TiO2 nanotubes, which were subsequently employed as a novel and efficient catalyst for the oxidation of salicylic acid (SA) for the first time. The effects of the cathodic current and reduction time on the electrocatalytic activity of the reduced TiO2 were investigated, and the results revealed that the optimal electrochemical treatment conditions were −5 mA cm−2 for 10 min. The electrochemically treated TiO2 nanotubes possessed a much higher overpotential for oxygen evolution than a commercial Pt electrode, and exhibited a high electrocatalytic activity in the oxidation of SA. When compared with a Pt electrode, the electrochemically treated TiO2 nanotubes exhibited ca. 6 times higher activity toward the oxidation of SA. The high electrocatalytic activity and stability of the treated TiO2 nanotubes enabled by the facile electrochemical reduction may be attributed to the decrease of Ti(IV), the increase of Ti(II) and Ti(III), and the increase of oxygen vacancies, as well as a significant improvement in the donor density. The effects of TiO2 nanotube length on its activity in the electrocatalytic oxidation of lignin were also studied. The TiO2 nanotubes were grown in a DMSO and 2% HF solution, where a constant potential was applied for different time intervals. A very uniform increase in the lengths of the nanotubes was observed when the anodization time interval was increased. The increase in the nanotube length had a very significant effect on the electrochemical oxidation of lignin. The rate of lignin oxidation continued to increase until an optimal length was achieved. Impedance studies revealed that there was an optimal length of nanotube that demonstrated the least charge transfer resistance; if longer nanotubes were grown a higher resistant was obtained. The fabricated electrode also showed a very high level of stability. Nanoporous TiO2 was directly grown employing a three-step electrochemical anodization process in ethylene glycol + 0.3 wt% NH4F + 2 wt% H2O. A significant enhancement in the photocatalytic activity of nanoporous TiO2 was achieved via a facile electrochemical reduction. Subsequently, the treated nanoporous TiO2 was investigated as a catalyst for photoelectrochemical water splitting and the photoelectrochemical oxidation of Rhodamine B (Rh B), which is an organic dye pollutant. Due to the presence of higher degree of ordering and a larger surface area, the nanoporous TiO2 electrode showed a much higher photocurrent under UV light in contrast to TiO2 nanotubes. The photocurrent of the as-prepared nanoporous TiO2 was 7.70 mA cm−2 at 1.5 V, and it was significantly increased to 46.23 mA cm−2 following additional electrochemical treatment. The electron donor density of the electrochemically treated nanoporous TiO2 was four orders of magnitude higher than that of the untreated nanoporous TiO2. The treated nanoporous TiO2 also demonstrated six times more rapid photoelectrochemical degradation of Rh B, as well as remarkable stability. The high surface area of electrochemically reduced nanoporous TiO2 may be used as a substrate to synthesize a Pt and Pb co-deposited bifunctional electrode (PtPb/EC-TiO2) to enable photo-assisted methanol oxidation in a direct methanol fuel cell (DMFC). Photochemical deposition was employed to introduce Pt and Pb onto the nanoporous TiO2 surface at an equimolar ratio. Mott-Shottky plots and Nyquist plots revealed that the PtPb/EC-TiO2 bifunctional electrode showed a higher electron donor density and a much lower charge transfer resistance as compared to the Pt/EC-TiO2, whether in the dark or under solar light irradiation. PtPb/EC-TiO2 exhibited a further enhancement in activity when solar light irradiation is applied to the electrode thus making it an efficient bifunctional electrode. III The simplicity and efficacy of the novel electrochemical reduction approach developed in this study facilitates the integration of TiO2 nanostructured materials into the design of high-performance energy harvesting and water purification technologies.
Keywords: Nanotechnology; Nanomaterials; TiO2 nanostructured materials; Nanotechnology in environmental applications; Noble metal atoms for fuel cell applications